2021
DOI: 10.1007/s41959-021-00053-9
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education in Indonesian higher education: mapping literature from the Country’s perspective

Abstract: Entrepreneurship education has become an important and fast-growing research area contributing to understanding and acknowledging global and national trends and developing future educational policies and actions. From the country’s perspective, the development of entrepreneurship education in Indonesia is relatively recent. This circumstance is reflected by the minimal amount of research in English language articles published in prominent journals, the uneven provision programs, and the lack of modern practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 98 publications
(91 reference statements)
0
20
0
2
Order By: Relevance
“…It is observed that the earlier the students are exposed to EE, the more they consider entrepreneurship as a career option at some point in their lives (Wilson, 2008). EE is considered a phenomenon that has grown globally over the last half a century (Amalia & von Korflesch, 2021). This has raised the demand for teachers involved in EE (Wu & Wu, 2017).…”
Section: Entrepreneurship Teachingmentioning
confidence: 99%
“…It is observed that the earlier the students are exposed to EE, the more they consider entrepreneurship as a career option at some point in their lives (Wilson, 2008). EE is considered a phenomenon that has grown globally over the last half a century (Amalia & von Korflesch, 2021). This has raised the demand for teachers involved in EE (Wu & Wu, 2017).…”
Section: Entrepreneurship Teachingmentioning
confidence: 99%
“…The implementation of education regarding entrepreneurship within higher education still has room for further development, especially in teaching methods and learning organizations (Amalia & von Korflesch, 2021). Teaching methods in universities about business people pedagogy must be developed within the framework of developing knowledge and directed at project-based learning that allows students to explore their business environment (Radianto & Wijaya, 2017).…”
Section: The Role Of Family Environment On Entrepreneurial Intentionmentioning
confidence: 99%
“…The online learning should be applied to the education process. In Indonesia, the HEI has already fully aware of the importance of entrepreneurship education (Amalia & Korflesch, 2021;Noya & Setiyati, 2015). Based on the awareness on how important the entrepreneurship education is, the online education process is being done.…”
Section: Introductionmentioning
confidence: 99%